Systematic Differences in HIV, Syphilis and Risk Behaviors among Street Based and Establishment Based Female Sex Workers in Kathmandu Valley of Nepal (Nepal Journal of Epidemiology, 2017)
Background: Female Sex Workers (FSWs) are main drivers of the HIV epidemic in Nepal. The work environment of sex work in Nepal is differentiated into establishment based (e.g. massage parlors, dance restaurants, hotels and lodges) and street based (e.g. streets, parks and markets). The study compares HIV, syphilis and risk behaviours among establishment-based FSWs and street-based FSWs in Kathmandu Valley of Nepal.Materials and Methods: Cross-sectional bio-behavioral surveys in 2006, 2008, 2011 and 2015 aimed to sample 2093 FSWs using two stage cluster sampling in the Kathmandu valley. Statistical analysis used chi-squared tests and logistic regression models to assess differences of HIV, syphilis and risk behaviors among street-based FSWs and establishment-based FSWs.Results: The study included 39.7% street-based FSWs and 60.3% establishment-based FSWs. The street-based FSWs had lower education levels, older age groups, separated, longer duration of sex work and inconsistent condom used with clients than establishment-based FSWs (p